Arteries are finely tuned thermosensors regulating myogenic tone and blood flow - Phan, Thieu; Sahibzada, Niaz; Freichel, Marc; Miyares, Rosa L.; Ahern, Gerard P. (Proceedings of the National Academy of Sciences of the United States of America, 2025)
In response to changing blood pressure, arteries adjust their caliber to control blood flow. This vital autoregulatory property, termed vascular myogenic tone, stabilizes downstream capillary pressure. Here, we reveal that tissue temperature, combined with intraluminal pressure, critically determines myogenic tone. Heating steeply activates tone in skeletal muscle, gut, brain, and skin arteries with temperature coefficients (Q10) of ~11 to 20. Each of these tissues has a distinct resting temperature, and we find that arterial thermosensitivity is tuned to this temperature, making myogenic tone sensitive to small thermal fluctuations. Interestingly, temperature and intraluminal pressure are sensed largely independently and the signals integrated to trigger myogenic tone. We demonstrate that thermosensitive channels TRPV1 and TRPM4 mediate heat-induced tone in skeletal muscle arteries with discrete temperature sensitivities. Similarly, TRPM4 contributes to heat-induced tone in gut and brain arteries. The half-maximal responses occur at approximately 31 °C for TRPV1 and 33 °C for TRPM4. Variations in tissue temperature are known to alter blood fluidity and therefore vascular conductance; remarkably, thermosensitive tone counterbalances this effect, thus protecting capillary integrity and fluid balance. In conclusion, thermosensitive myogenic tone is a fundamental homeostatic mechanism regulating tissue perfusion.
Online veröffentlicht: 20. Mai 2025
Gesehen am 15.09.2025